Damage analysis of Golyazi Apartments building failed under axial loads: A case study in Konya, Turkey. (April 2021) - Nakipoglu, Abdulhamit; Unal, Alptug; Kamanli, Mehmet
Highlights: A 6-storey hybrid building's basement columns were damaged under axial loads. There were creep damage, buckled reinforcements and corrosion damage. General damage analysis and creep analysis was made for the damaged columns. The building was modeled by ANSYS structural analysis program. Existing and possible damages were also investigated analytically. Abstract: This study is in the characteristics of a case study. In this study, damage analysis has been made to the Golyazi Apartments Block A building and the causes of the damages were investigated. The building is located in Konya/Turkey. It has some damaged vertical load bearing elements as a result of various effects. The damage was first detected by the residents in September 2018. Creep and axial load analyzes were carried out in the building through ETABS and ANSYS structural analysis programs and crack/damage checks were made analytically for the existing damage situation and for new damages that might occur. At the end of the study, it has been observed in some of the columns in the humid basement of the building that load bearing capacities were exceeded due to creep, axial compressive loads and corrosion effects and severe damages occurred. In addition, ANSYS analysis results coincide with existing building damage. Although no damage occurred in some of the columns of the structure, damage was observed in the same columns in the ANSYS model. This situation might predict the future damage in the building that can happen. Finally, some measures that can be taken as a result of the identified damage situation are presented.